2023
DOI: 10.1002/smll.202303432
|View full text |Cite
|
Sign up to set email alerts
|

All‐Graphene Quantum Dot‐Derived Battery: Regulating Redox Activity Through Localized Subdomains

Abstract: In the quest for materials sustainability for grid‐scale applications, graphene quantum dot (GQD), prepared via eco‐efficient processes, is one of the promising graphitic‐organic matters that have the potential to provide greener solutions for replacing metal‐based battery electrodes. However, the utilization of GQDs as electroactive materials has been limited; their redox behaviors associated with the electronic bandgap property from the sp2 carbon subdomains, surrounded by functional groups, are yet to be un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…And the peak of ‐COOLi shifts to 1401 cm −1 in LESG, similar to the EELS results [35] . Furthermore, Time‐of‐Flight Secondary Ion Mass Spectrometry (TOF SIMS) also reveals the presence of COOLi in LEG (Figure S8) [36] . Therefore, it is inferred that Li elements are incorporated into the graphite as COOLi during the lithium pre‐storage process.…”
Section: Resultssupporting
confidence: 77%
“…And the peak of ‐COOLi shifts to 1401 cm −1 in LESG, similar to the EELS results [35] . Furthermore, Time‐of‐Flight Secondary Ion Mass Spectrometry (TOF SIMS) also reveals the presence of COOLi in LEG (Figure S8) [36] . Therefore, it is inferred that Li elements are incorporated into the graphite as COOLi during the lithium pre‐storage process.…”
Section: Resultssupporting
confidence: 77%
“…[35] Furthermore, Time-of-Flight Secondary Ion Mass Spectrometry (TOF SIMS) also reveals the presence of COOLi in LEG (Figure S8). [36] Therefore, it is inferred that Li elements are incorporated into the graphite as COOLi during the lithium pre-storage process. Both EELS and FTIR analyses indicate a lower bond energy for COOLi in LESG compared to LEG.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent research has reported controlled redox sites in LIBs where GQDs are introduced into every component of the battery. 29 In this study, the anode was prepared through π–π stacking between non-oxidized graphene flakes (NOGF) and GQDs, while the cathode was prepared through the selective esterification reaction between the carboxyl groups of GQDs and phenoxazine (PXZ). This resulted in a metal-free battery with an energy density of 290 W h kg cathode −1 (160 W h kg cathode+anode −1 ) and stable cycling for over 1000 cycles.…”
Section: Applications Of Gqdsmentioning
confidence: 99%
“…17–19 Moreover, GQDs exhibit outstanding reactivity based on solvent dispersibility and physicochemical adsorption capabilities. 20,21 As a result, GQDs have garnered significant attention in various applications, including biotechnology, 22–24 water purification, 25,26 catalysis, 20,27,28 energy storage, 29–32 and displays. 33,34…”
Section: Introductionmentioning
confidence: 99%